Ex vivo T‐cell depletion vs post‐transplant cyclophosphamide, sirolimus, and mycophenolate mofetil as graft‐vs‐host disease prophylaxis for allogeneic hematopoietic stem cell transplantation. (18th October 2020) - Montoro, Juan; Roldán, Elisa; Piñana, José Luis; Barba, Pere; Chorão, Pedro; Quintero, Abdiel; Hernani, Rafael; Ortí, Guillermo; Lorenzo, José Ignacio; Balaguer‐Roselló, Aitana; Salamero, Olga; Fox, Laura; et al.
Abstract: Objective: To compare the efficacy and safety of CD34+ selected ex vivo T‐cell depletion (TCD) vs post‐transplant cyclophosphamide, sirolimus, and mycophenolate mofetil (PTCy‐Sir‐MMF) as graft‐vs‐host disease (GVHD) prophylaxis. Methods: We retrospectively included patients who underwent allogeneic hematopoietic stem cell transplantation (allo‐HSCT) with either TCD (n = 38) or PTCy‐Sir‐MMF (n = 91). Results: Cumulative incidence of neutrophil and platelet recovery was 92% vs 99% ( P = .06) and 89% vs 97% ( P = .3) in TCD and PTCy‐Sir‐MMF, respectively. Cumulative incidences of aGHVD grade II‐IV, III‐IV, and moderate to severe cGVHD were 11% vs 19% ( P = .2), 3% vs 2% ( P = .9), and 3% vs 36% ( P < .001) in TCD and PTCy‐Sir‐MMF, respectively. The 2‐year non‐relapse mortality, relapse, disease‐free and overall survival were 25% vs 8% ( P = .01), 20% vs 16% ( P = .2), 55% vs 76% ( P = .004), 57% vs 83% ( P = .004) for TCD and PTCy‐Sir‐MMF, respectively. Cumulative incidence of cytomegalovirus and Epstein‐Barr infection requiring therapy was 76% vs 40% ( P < .001) and 32% vs 0% ( P < .001) in TCD and PTCy‐Sir‐MMF, respectively. PTCy‐Sir‐MMF platform showed faster T‐cell reconstitution. Conclusions: PTCy‐Sir‐MMF provides better survival outcomes but is associated with higher risk of cGVHD compared to TCD.